Aligning policy through inclusive multi-level governance in local development planning - Rifka Akibu; Franky Djafar (Otoritas : Jurnal Ilmu Pemerintahan, 2026)
Development disparities in Indonesia, particularly in Gorontalo Province, continue to be influenced by weak coordination between the central and local governments. Although decentralization and participatory planning have been widely discussed, attention to how intergovernmental coordination functions in regional development planning and how community participation is effectively integrated into these processes remains limited. This study examines multi-level governance in regional development planning in Gorontalo Province. Using a qualitative case study design, data were collected through semi-structured interviews with ten key informants, field observations, and document analysis conducted between January and March 2024. Data were analyzed thematically to identify patterns of vertical coordination, institutional capacity, community participation, and oversight mechanisms. Results show that overlapping jurisdictions, limited local institutional capacity, and unequal access to participatory forums such as Development Planning Consultation reduce policy responsiveness and implementation effectiveness. This study suggests that strengthening coordination mechanisms, enhancing local administrative capacity, and expanding access to participatory forums can support more inclusive local development planning. This article contributes empirical insights into how cross-level governance challenges are experienced within a decentralized regional context   .